A Closer Look at Anandamide Interaction With TRPV1 - Muller, Chante; Lynch, Diane L.; Hurst, Dow P.; Reggio, Patricia H. (Frontiers in Molecular Biosciences, 2020)
The transient receptor potential subfamily vanilloid type 1 ion channel (TRPV1), located in the peripheral nervous system has been implicated in the perception of pain and possesses the ability to be modulated by various cannabinoid ligands. Because of its location, TRPV1 is an ideal target for the development of novel pain therapeutics. Literature precedent suggests a wide range of cannabinoid ligands can activate TRPV1, but the location and mode of entry is not well understood. Understanding the modes in which cannabinoids can enter and bind to TRPV1 can aid in rational drug design. The first endogenous ligand identified for TRPV1 was the endocannabinoid, anandamide (AEA). The Molecular Dynamics (MD) studies discussed here investigate the entry mode of AEA into TRPV1. During the course of the 10+ microsecond MD simulations, two distinct binding modes were observed: AEA binding in the tunnel formed by the S1-S4 region, and AEA binding in the vanilloid binding pocket, with preference for the former. Unbiased MD simulations have revealed multiple spontaneous binding events into the S1-S4 region, with only one event of AEA binding the vanilloid binding pocket. These results suggest that AEA enters TRPV1 via a novel location between helices S1-S4 via the lipid bilayer.